Goal-setting Capacity Scale - Measures for Advancing Gender Equality (MAGNET) Initiative (International Food Policy Research Institute, 2024)
The Measures for Advancing Gender Equality (MAGNET) initiative aims to broaden and deepen the measurement of women’s agency, based on the development of new tools and rigorous testing and comparison of both new and existing methods for measuring agency, and promoting the adoption of these measures at scale. By increasing the availability of innovative meaningful measures of agency for a broad range of contexts, we hope our work will lead to an improved understanding of what women’s agency is, how it manifests and how it can best be measured across contexts given the research question at hand. Improving women’s ability to define goals and act on them is an important and urgent policy goal. Yet our understanding of how to achieve this goal is hampered by the lack of adequate measurement tools and recognized best practices. The 8-item Goal-setting Capacity Scale allows researchers to capture an individual’s goal-setting capacity. Goal-setting capacity is a process that establishes specific, time-based behaviors that are measurable, achievable, and realistic. They can be related to both economic and non-economic activities. In terms of timing, they can be short-term (e.g., saving money for a small household purchase, learning a new skill) or long-term (e.g., saving money for a large household purchase, achieving some level of education). Other variables that you may want to collect alongside goal-setting capacity are education level, employment status, age, and MAGNET’s livelihoods self-efficacy scale. This data study includes following files. 1. A survey document (including implementation guidelines). 2. A statistical annex containing more information about the validation of the tool, as well as statistical guidance for analysis. 3. Two files, CAPI_Choices and CAPI_Survey, along with the accompanying help files, can be used to construct a CAPI program ready for survey implementation. Alternatively, users can use an Excel workbook "CAPI_.xlsx" that includes worksheets for survey and choices, along with help files, for constructing a CAPI program ready for survey implementation.